Les trames vertes et bleues habitantes : un cheminement entre pratiques et représentations. L’exemple de la ville de Paris (France) - Étienne Grésillon; Marianne Cohen; Julien Lefour; Lydie Goeldner; Laurent Simon (Développement Durable et Territoires)
Considering the green and blue corridors (TVB) of Paris delimitated by floral inventories and works in the field of geomatics, the study tried to understand both the usage as well as the perception of these areas. In this densely populated (20 807 inhabitants per km2), densely built-up (41 %), and only little extended (105 km2) matrix the Parisians conceive these areas as places for respiration and liberty. Their perception of these areas is even more linked to their usage than to their social categories. The variables of gender, age or educational level do only interfere with their perception if they influence the usage made by the inhabitants. Two visions of TVB are emerging, one recognizing the strong link between man and nature and the other postulating their differences. In the first one, the TVB must be defended in the city because it is part of the everyday life of the people and in the other one they do not have their place in a metropolis like Paris. These results can be useful in the moment of the implementation of the politics of green and blue corridors at Paris.